DETERMINATION OF EMPLOYEE BURNOUT ON EMPLOYEE WELL BEING WITH ARTIFICIAL INTELLIGENCE AS MODERATION FOR INDONESIAN SHARIA BANK EMPLOYEES - DJ, Yunni Rusmawati; Azizah, Luluk Nur; Najiah, Evi Fitrotun (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
Syariah Banks were established without mentioning ordinary banking because the parent bank is Sharia Commercial Banks, which has now established 12 banks in its development. With the merger of bank employees, it takes some time to adapt to the new system so that employees experience burnout. Artificial Intelligence is the study of how computers perform intelligent tasks that previously could only be done by humans. Burnout as an inhibiting factor in the variable employee well-being and artificial intelligence is a supporting factor in achieving employee welfare. The purpose of this research is to find out: (1) Determinants of Employee Burnout on Employee Well Being at Bank Syariah Indonesia Employees, (2) Determinants of Employee Burnout on Employee Well Being with Artificial Intelligence as Moderation for Indonesian Sharia Bank Employees. The findings support the mediating role of artificial intelligence in the relationship between burnout and employee well-being. The results in this study Use Information from Conservation and Resource Allocation. Theoretically, this study not only examines the direct relationship between perceived talent identification and burnout, but also provides insight into why identifying perceived talent makes a difference in employee outcomes. The practical implication in this research is that it provides management views that must pay attention to the process of developing mobile Internet, which has led to more and more application scenarios that can be considered as to the impact of improving employee well-being.